Calculation Analysis-The Concept of Object Acceleration on a Simple Machine with an Inclined Plane Pulley System - Mahmudah, Huraiza; Mahrus (International Journal of Science Education and Science, 2025)
Natural science (science) is a branch of knowledge related to how to systematically find out about nature. Science has components consisting of products, processes and attitudes. This experimental study aims to determine the factors that affect the magnitude of the acceleration of objects on a simple plane with an inclined plane pulley system. The type of research used is experimental research using an inclined plane pulley system as an aid. Based on the six experiments of the inclined plane pulley system that have been carried out, the results of the study show that there are several factors that influence the magnitude of the acceleration of objects on simple planes of the inclined plane pulley system, including: the mass of the object, the pulling/pushing force, the slope of the plane (angle size), and the friction coefficient for rough/slippery surfaces. In addition, the value of the acceleration due to gravity somewhere can also affect the magnitude of the object's acceleration. However, because the value of the acceleration due to gravity in various places is the same, the value does not really affect it. The magnitude of the acceleration due to gravity is a constant g 9.8 m/s2 or is often rounded up in calculations to g 10 m/s2.